2018
DOI: 10.1080/15438627.2018.1447468
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of kinesiology taping on temperature distribution at the site of application

Abstract: The aim of the study was to assess skin temperature after short-term kinesiology tape application. Seventy-four healthy volunteers with no history of lower back pain participated in the study. Kinesiology tape was applied in the experimental group, and Matopat Classic adhesive tape was applied in the placebo group. Study participants wore the tape for four consecutive days and were then thermographically analyzed for changes in skin temperature. Examination of skin surface temperature distribution revealed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
0
13
1
1
Order By: Relevance
“…Previous studies have shown that the skin surface temperature is closely related to subcutaneous perfusion and tissue metabolism and that skin infrared thermal radiation may reflect an increase or a decrease in local skin perfusion flow rates (Slomka et al, 2018). In this study, after using two different taping materials, we found the temperature difference at the waist in Kfan was significantly higher than that of no taping, but this was not observed with Afan.…”
Section: Effects Of Two Different Fan-strip Materials On Skin Temperacontrasting
confidence: 45%
See 3 more Smart Citations
“…Previous studies have shown that the skin surface temperature is closely related to subcutaneous perfusion and tissue metabolism and that skin infrared thermal radiation may reflect an increase or a decrease in local skin perfusion flow rates (Slomka et al, 2018). In this study, after using two different taping materials, we found the temperature difference at the waist in Kfan was significantly higher than that of no taping, but this was not observed with Afan.…”
Section: Effects Of Two Different Fan-strip Materials On Skin Temperacontrasting
confidence: 45%
“…Only the researcher and participant were permitted to enter. The indoor temperature was adjusted to 24.5 ± 0.5 • C, The indoor humidity was controlled at 40% (Sillero Quintana et al, 2015;Slomka et al, 2018). In addition, we also monitored the indoor atmospheric pressure and body temperature changes of the participants.…”
Section: Laboratory Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Slomka et al [44] utilizaram um protocolo de estudo com 60 participantes analisando alterações da temperatura local da pele após uso da bandagem elástica em um curto período e, confirmaram uma mudança de temperatura estatisticamente significativa em todas as áreas avaliadas, o que condiz com o presente estudo.…”
Section: Discussionunclassified